Characterization of nucleic acids from extracellular vesicle-enriched human sweat - Bart, Geneviève; Fischer, Daniel; Samoylenko, Anatoliy; Zhyvolozhnyi, Artem; Stehantsev, Pavlo; Miinalainen, Ilkka; Kaakinen, Mika; Nurmi, Tuomas; Singh, Prateek; Kosamo, Susanna; Rannaste, Lauri; Viitala, Sirja; et al. (My University, 2021)
The human sweat is a mixture of secretions from three types of glands: eccrine, apocrine, and sebaceous. Eccrine glands open directly on the skin surface and produce high amounts of water-based fluid in response to heat, emotion, and physical activity, whereas the other glands produce oily fluids and waxy sebum. While most body fluids have been shown to contain nucleic acids, both as ribonucleoprotein complexes and associated with extracellular vesicles (EVs), these have not been investigated in sweat. In this study we aimed to explore and characterize the nucleic acids associated with sweat particles.
Keywords: extracellular vesicles; skin; sweat; genomics; microbiome; iho; hikoilu